RNA degradation in antiviral immunity and autoimmunity. Issue 3 (March 2015) - Rigby, Rachel E.; Rehwinkel, Jan
Highlights The nonsense-mediated decay (NMD) pathway defends cells against RNA virus invasion. NMD targets viral RNAs for degradation, including by the RNA exosome. Genetic deficiencies in NMD and RNA exosome components cause autoimmunity. NMD and the RNA exosome prevent aberrant activation of innate immune responses.